2013
DOI: 10.1097/rct.0b013e3182772d66
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative DTI Assessment in Human Lumbar Stabilization Muscles at 3 T

Abstract: The DTI metrics in paraspinal muscles can be reliably measured and are influenced by body mass index and weight but not by age or physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Galban et al found a significantly higher diffusivity in muscles of female subjects as compared to males; however, no clear explanation could be given. Moreover, these findings seem to be more pronounced in the flexor muscles, but cannot be reproduced by others . With respect to age, an overall decrease in diffusivity and increase in FA values in calf muscles has been found with increasing age, which is hypothesized to be caused by age‐induced atrophy .…”
Section: Feasibility Studies and Reported Variances In Healthy Skeletmentioning
confidence: 99%
See 3 more Smart Citations
“…Galban et al found a significantly higher diffusivity in muscles of female subjects as compared to males; however, no clear explanation could be given. Moreover, these findings seem to be more pronounced in the flexor muscles, but cannot be reproduced by others . With respect to age, an overall decrease in diffusivity and increase in FA values in calf muscles has been found with increasing age, which is hypothesized to be caused by age‐induced atrophy .…”
Section: Feasibility Studies and Reported Variances In Healthy Skeletmentioning
confidence: 99%
“…Moreover, these findings seem to be more pronounced in the flexor muscles, but cannot be reproduced by others. 17,94,99 With respect to age, an overall decrease in diffusivity and increase in FA values in calf muscles has been found with increasing age, which is hypothesized to be caused by age-induced atrophy. 88 However, reported changes differ per muscle(-group) (flexors/ extensors or lower/upper extremities), sometimes are absent, or contradictory between studies.…”
Section: Sensitivity To Demographic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of muscle architecture noninvasively to gain insight into the underlying fibre structure has been carried out for over a decade using diffusion tensor imaging [83][84][85][86][87][88][89][90][91][92][93]. While earlier DTI studies were performed in the brain to assess the integrity of cerebral structures [94,95], the technique was quickly applied to investigate skeletal muscles due to the anisotropic muscle fibre structure.…”
Section: Other Advanced Structural and Functional Mri Techniques Diffmentioning
confidence: 99%